The bullet that missed eaudiobook - Osman, Richard (Thursday Murder Club Mystery, 2022)
The third installment in the beloved and New York Times bestselling series from Richard Osman, also author of We Solve Murders “The quartet of aging amateur sleuths…remain wonderful company.” — The New York Times Book Review It is an ordinary Thursday, and things should finally be returning to normal. Except trouble is never far away where the Thursday Murder Club are concerned. A decade-old cold case—their favorite kind—leads them to a local news legend and a murder with no body and no answers. Then a new foe pays Elizabeth a visit. Her mission? Kill or be killed. Suddenly the cold case has become red hot. While Elizabeth wrestles with her conscience (and a gun), Joyce, Ron, and Ibrahim chase down the clues with help from old friends and new. But can the gang solve the mystery and save Elizabeth before the murderer strikes again? From an upmarket spa to a prison cell complete with espresso machine to a luxury penthouse high in the sky, this third adventure of the Thursday Murder Club is full of the cleverness, intrigue, and irresistible charm that readers have come to expect from Richard Osman’s bestselling series. “ The Bullet That Missed hits on every front. ” —the Wall Street Journal